PENGARUH CORPORATE GOVERNANCE, FINANCING TO DEPOSIT RATIO DAN NON PERFORMING FINANCINNG TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DENGAN CAPITAL ADEQUACY RATIO SEBAGAI VARIABEL INTERVENING - Supriadi, aris (Pascasarjana Universitas Sultan Ageng Tirtayas, 2021)
This study aims to examine the effect of CG as seen from the results of self-assessment and FDR, NPF on profitability as an indicator in assessing the performance of Islamic banking with CAR as an intervening variable. This research is a quantitative research. The type of data used in this research is secondary data. The data is processed using the SPSSv.20 program by using a multiple linear regression approach.the results showed that Corporate Governance had a significant positive effect on profitability. Financing To Deposit Ratio has a significant positive effect on profitability. Non-Performing Financing has a significant negative effect on profitability. Capital Adequacy Ratio has a significant positive effect on profitability. Corporate Governance has a positive effect on the Capital Adequacy Ratio. Financing To Deposit Ratio does not have a positive effect on the Capital Adequacy Ratio. Non-Performing Financing has a significant positive effect on the Capital Adequacy Ratio. Corporate Governance does not have a positive effect on profitability through the Capital Adequacy Ratio. Financing To Deposit Ratio has an effect on Profitability through the Capital Adequacy Ratio. Non-performing Financing has no effect on profitability through the Capital Adequacy Ratio.